ASESMEN KINERJA (PERFORMANCE ASSESSMENT) DALAM PEMBELAJARAN MATEMATIKA - Suci Yuniati (An-Nida', 2011)
The system for assessment in mathematics is dominated by a single method of assessment that is paper and pencil test that only measures students' memories of factual information and procedures of the algorithm alone. Its domination can be seen from the questions the National Examination (UN) and the National Selection Entry State University (SNMPTN). The use of the objective tests in these matters encourages teachers to give similar exercises to students as they have to answer the questions of this form. Even the students are taught "tricks" how to solve such problems. In fact, what are the appropriate and proper methods for collecting information about students' understanding and skills in mathematics? However, to overcome the limitations of current evaluation methods and teachers can obtain complete and comprehensive information about students, attendance and assessment performance assessment is needed. Assessment is a systematic process to obtain information about studying and learning. Assessment of performance is an assessment that requires students to demonstrate performance, not to answer or choose an answer from a range of possible answers that are already available. Performance assessment can be used to obtain information about the mathematical knowledge, strategic knowledge and mathematical communication. In this paper, he writer will present one method of assessment of performance assessment that can be used as an alternative method of assessment for teachers.